Safety of allergen immunotherapy in patients with SARS-CoV-2 infection - Atayık, Emel; Aytekin, Gökhan (The European Research Journal, 2022)
Objectives: The aims of presenting study were trying to expose the course of SARS-CoV-2 (severe acute respiratory syndrome–related coronavirus) in patients with allergic rhinitis (AR), to compare the prevalence of SARS-CoV-2 infection, hospitalization and pneumonia rates in patients with AR receiving allergen immunotherapy (AIT) and patients did not receiving AIT (non-receivers) and to define possible risk factors for SARS-CoV-2 positivity in patients with AR. Methods: A total of 419 patients with AR who were being followed-up in a tertiary allergy clinic between June 1, 2020 and December 31, 2020, were selected for the study. Results: Seventy-nine (18.9%) patients became infected with the SARS-CoV-2 [32 (19.6%) patients in AR patients with AIT and 47 (18.4%) patients in non-receivers] and the rate of pneumonia was 2.4% [12.7% of SARS-CoV-2 (+) patients]. There was no significant difference was determined between the AR patients with AIT and the non-receivers in regard of the rate of SARS-CoV-2 infection, pneumonia and hospitalization (p = 0.864, p = 0.055 and p = 0.075; respectively). There was a significant difference between the groups in terms of gender, duration of disease, sensitivity to allergens (atopy) and serum IgE levels (p = 0.009, p = 0.001, p = 0.001 and p = 0.001; respectively). The accompanying comorbidities, eosinophil cout, AIT and duration of AIT were not found to be associated with an increased risk SARS-CoV-2 PCR positivity. However, female gender was shown to be associated with an decreased risk for SARS-CoV-2 PCR positivity (OR, 0.571; 95% confidence interval, 0.330-0.987; p = 0.045). Conclusions: The course of SARS-CoV-2 is similar in patients with AR who underwent AIT and patients with AR who did not undergo AIT, and AIT does not seem to increase the risk for SARS-CoV-2 infection.